Diary of a wimpy kid [videorecording (DVD)] - Freudenthal, Thor; Gordon, Zachary, 1998-; Capron, Robert, 1998-; Harris, Rachael, 1968-; Bostick, Devon, 1991-; Moretz, Chloë, 1997-; Zahn, Steve, 1968-; Kinney, Jeff (20th Century Fox Home Entertainment, 2010)
The hysterically funny, best-selling book comes to life in this smash-hit family comedy! Greg Heffley is headed for big things, but first he has to survive the scariest, most humiliating experience of any kid's life, middle school! That won't be easy, considering he's surrounded by hairy-freckled morons, wedgie-loving bullies and a moldy slice of cheese with nuclear cooties!